The Therapeutic and Nutritive Potential of the Edible Fixed Oils - Kaur, Loveleen; Garg, Madhukar; Arora, Athrv; Yoonus Thajudeen, Kamal; Vaid, Lavish; Kaur, Jasleen; Salam, Shahana; Chopra, Hitesh (Scripta Medica, 2025)
Edible oils have been extensively consumed foods derived from different vegetables and animal parts. Approximately 96 % composed of triacyl glycerides, consisting of a variety of fatty acids, phospholipids, phytosterols, tocopherols, antioxidants and waxes. It accounted for a large portion of Indian household food expenditure and long been known for their medicinal and nutritional benefits. Data on therapeutic activity of edible oil were collected and compiled from scientific databases like Google Scholar and PubMed. This review intended to include the healthcare benefits as well as the nutritional value of the oils. It provided an overview of the therapeutic value of the edible oils including anti-ageing, antioxidant, anti-inflammatory and anti-cancer properties. Additionally, edible oils might help mitigating the risk of heart disease, reduced formation of kidney stones and lower bad cholesterol levels. It examined a variety of oils such as soybean, sesame, sunflower, olive, palm, flax seed, corn and coconut oil. Furthermore, it indicated that edible oils provide humans with a significant quantity of phytochemicals, vitamin E and fatty acids which are necessary for good health. It could be stipulated that edible oils provide both energy and nutrients for growth and metabolism as well as being used for numerous therapeutic and food applications.